1997
DOI: 10.1046/j.1570-7458.1997.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Weather‐induced changes in moth activity bias measurement of long‐term population dynamics from light trap samples

Abstract: Interpretation of light trap catches of moths is complicated by daily variation in weather that alters flight activity and numbers caught. Light trap efficiency is also modified by wind and fog, and daily weather may effect absolute abundance (numbers actually present). However, actograph experiments and other sampling methods suggest that changes in daily activity are large by comparison to changes in absolute abundance. Daily variation in weather (other than wind and fog) is therefore a form of sampling erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 29 publications
5
34
0
1
Order By: Relevance
“…This result was similar to the result reported by Muirhead-Thomson (1991) that the BLTs had consistently caught a higher abundance and greater variety of insects during mid April to mid August than other traps. Similar results by (Mellanby, 1939;Holyoak, et al, 1997) showed that the higher insects were trapped from mid- May to the end of August. This may be because the higher temperature (Fig 5) increases flight activity and the numbers present in an area of both species and individuals.…”
Section: Insect Numberssupporting
confidence: 80%
“…This result was similar to the result reported by Muirhead-Thomson (1991) that the BLTs had consistently caught a higher abundance and greater variety of insects during mid April to mid August than other traps. Similar results by (Mellanby, 1939;Holyoak, et al, 1997) showed that the higher insects were trapped from mid- May to the end of August. This may be because the higher temperature (Fig 5) increases flight activity and the numbers present in an area of both species and individuals.…”
Section: Insect Numberssupporting
confidence: 80%
“…We found the strongest relationship between moth abundance and the abundance of larvae collected from foliage in the species that were collected in the greatest abundance. Holyoak et al (1997) found that biased abundance estimates of moths collected by light traps were more likely in moth species with shorter ßight periods. Although pooled weekly abundance of moths collected in light traps may provide good estimates of annual abundance in well-represented species, less abundant species that are only present for a few weeks of the season may still be subjected to high sample error using this method.…”
Section: Discussionmentioning
confidence: 94%
“…Holyoak et al (1997) demonstrated that the sampling efficiency of light traps depended on a series of meteorological conditions. Holyoak et al (1997) demonstrated that the sampling efficiency of light traps depended on a series of meteorological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Vertical stratification of diversity has been mainly addressed in Lepidoptera (e.g. In contrast, daily variations in diversity caused by weather are only reported for Lepidoptera collected in light traps ( Holyoak et al , 1997 ), but the variations may also be derived from differences in the dispersal ability or mobility of species. Odegaard, 2004;Charles & Bassett, 2005 ).…”
Section: Introductionmentioning
confidence: 99%